PENGARUH MODAL, LOKASI DAN JAM KERJA TERHADAP TINGKAT PENDAPATAN PEDAGANG DI WISATA PANTAI SELATBARU KECAMATAN BANTAN DALAM PERSPEKTIF EKONOMI ISLAM - Novia Sari; Sandi Andika (STAIN Bengkalis, 2020)
Trade is the main root of national development and regional development, which aims to create an advanced and independent society and physically and mentally prosperous. The goal of traders is to get high income to meet their needs. Several factors that affect the level of income include capital, location and working hours. The purpose of this study was to determine the effect of capital, location and working hours on the income level of traders. A questionnaire in the form of a questionnaire was used to collect data. The total population of the study was all traders in Selatbaru Beach, which consisted of 40 people, all of whom were used as research samples. In analyzing data; Researchers used multiple linear regression quantitative analysis. Hypothesis testing using the t test shows that